Catalyst- and solvent-free bisphosphinylation of isothiocyanates: a practical method for the synthesis of bisphosphinoylaminomethanes. Issue 1 (7th December 2017) - Wen, Li-Rong; Sun, Yong-Xu; Zhang, Jin-Wei; Guo, Wei-Si; Li, Ming
Abstract : A new protocol for the construction of bisphosphinoylaminomethanes was developed through double addition of phosphine oxides to isothiocyanates. Abstract : A general and convenient double addition of phosphine oxides to isothiocyanates is described. It is a practically useful protocol for the construction of bisphosphinoylaminomethanes. The reaction can be carried out smoothly under metal- and solvent-free conditions. It also features a broad substrate scope, simple operation and purification. A possible mechanism involving a tandem double nucleophilic addition/H2 S elimination/ in situ imine reduction process is proposed.